(3JhKjb YQHi GdEjeGf aj JaVjd MHjH GdQMefs - (3GHf GdHGQRj , gHI Gddg Hf YHO GdQMje Hf EHQGgje, TQa GdOjf CHhGdbGSe,J (B738 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdYRI hGdSdWGf agPG cJGH JhKjb YQi GdEjeGf eQJH Ydi CQHYI CQcGf GdbSe GdChd ai GdeYLRGJ GdMSfjI s
(3BNQgG (B:s
(3JaSjQ CdaGX ef gPG GdMOjK hdg jMhi Ydjg GQbe Gi GSJOGQ Ydjg hHYO abO GfgjJ cJGHi Edi MOg hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3Hg CKGQ JbWjYs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B73 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B139s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs